Critical Thinking Profile of Chemistry Pre-Service Teachers in Pre-Laboratory Sessions - Devy Lestari; Endah Fitriani Rahayu; Rosi Oktiani (Magister Pendidikan Sains Universitas Sebelas Maret, 2025)
Critical thinking skills are essential for chemistry pre-service teachers, particularly in pre-laboratory sessions. However, many students struggle to apply these skills before conducting experiments. This study aims to analyze the critical thinking profile of chemistry pre-service teachers in pre-laboratory sessions, identifying key indicators that require improvement. This research adopts a quantitative descriptive approach with purposive sampling, involving 32 second-semester Chemistry Education students enrolled in the Basic Chemistry Practicum course. The research instrument consists of 40 multiple-choice questions based on Ennis' critical thinking indicators. Data were collected through pre-laboratory tests and analyzed using descriptive statistics to determine score distribution and categorize students' critical thinking levels. Results show that most students fall into the fairly good category (62.50%), while 15.62% reached the good category. The highest-scoring indicator was defining terms (81.250, good category), while analyzing arguments had the lowest score (48.125, less category). These findings indicate that students struggle with evaluating information and connecting theories to experimental outcomes. This study provides a specific analysis of critical thinking skills in pre-laboratory sessions, an area that remains underexplored. The findings support the need for inquiry-based learning, reflective discussions, and scientific argument evaluation to enhance critical thinking skills in chemistry pre-service teachers.